Using online tutorials to teach the accounting cycle. Issue 4 (18th May 2020) - Zhang, Tracey; Low, Lay-Chin; Seow, Poh-Sun
Abstract: The accounting cycle is an important yet difficult topic for introductory financial accounting students to learn. This problem motivates the authors to develop four innovative online tutorials with a coherent storyline to enable students to learn the accounting cycle and to supplement in-class learning. The survey results suggest that the accounting cycle online tutorials substantially improve students' perceived knowledge of the topic (an increase of 59.8% in the perceived knowledge) and the improvement is statistically significant. The results also indicate that the online tutorials are valued by students for increasing their interest in the course and providing the business context to understand the accounting cycle.